2020
DOI: 10.1177/0972063420937930
|View full text |Cite
|
Sign up to set email alerts
|

Association between Health Insurance and Incidence of Death in Stateless Children in Tak Province, Thailand

Abstract: This study assesses the association between health insurance and incidence of death in stateless children compared with uninsured children in Tak Province in Thailand. The study used electronic medical records of children aged between 0 and 15 who registered with selected health facilities between 01 January 2013 and 31 December 2017. The required data was obtained from ‘43-files database’ through the Provincial Public Health Office. The death case was used as a binary outcome variable while the exposure was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Our study confirms the findings of the limited existing literature that long distances, socioeconomic status, education, healthcare provider-related barriers, and healthcare system structure were the common problems preventing the hill tribe community from receiving or accessing proper health information and services. Consistent with a few prior studies on this population in Thailand residency in underserved and poverty areas results in the need for a full day to visit the hospital [13,[18][19][20]. Along with other international studies, the study found tribal people faced health disadvantages that resulted from insufficient health services targeted for their specific needs [16,31,32].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our study confirms the findings of the limited existing literature that long distances, socioeconomic status, education, healthcare provider-related barriers, and healthcare system structure were the common problems preventing the hill tribe community from receiving or accessing proper health information and services. Consistent with a few prior studies on this population in Thailand residency in underserved and poverty areas results in the need for a full day to visit the hospital [13,[18][19][20]. Along with other international studies, the study found tribal people faced health disadvantages that resulted from insufficient health services targeted for their specific needs [16,31,32].…”
Section: Discussionsupporting
confidence: 85%
“…As a result of the low EPI rate, in 2020, 6.71 hill tribe children per 100,000 population were reported to have measles infection with 24.8% of these children being under 5 years of age [17,18]. This is perhaps due to the many barriers hill tribe parents face in accessing in healthcare services for their children [18,19]. Not only is the risk for infectious disease high, but malnutrition is also a significant problem among hill tribe children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation